Health needs assessment for the double burden of malnutrition: a community-based study on nutrition facilitators and barriers in rural Tanzania - Victoria von Salmuth; Lieke Buijs; Bwire Chirangi; Anita CE Vreugdenhil; Onno CP van Schayck (Cambridge University Press, 2023)
Abstract Objective: The aim of this study is to explore nutrition-related health needs, the perceptions and beliefs regarding the double burden of malnutrition, as well as barriers and facilitators in accessing nutritious food among the local population in rural Tanzania. Design: A qualitative study design using semi-structured individual interviews and focus-group discussions (FGD) was used. Basic socio-demographic information was obtained from all participants. Setting: The study was conducted in four villages within the catchment area of the Shirati KMT Hospital in Rorya district, in north-western Tanzania. Participants: Men and women in the reproductive age as well as Community Health Workers (CHW) were included. Results: In total, we performed fourteen interviews (N 41), consisting of four FGD, one dual and nine individual interviews. The three most significant topics that were identified are the large knowledge gap concerning overweight and obesity as a health problem, changing weather patterns and its implications on food supply and the socio-cultural drivers including gender roles and household dynamics. Conclusion: Environmental and socio-cultural factors play a crucial role in the determinants for DBM, which underlines the importance of understanding the local context and the nutrition practices and beliefs of the communities. Future nutritional interventions should aim towards more inclusion of men in project implementation as well as support of women empowerment. CHW could play a key role in facilitating some of the suggested interventions, including nutritional counselling and increasing awareness on the drivers of the double burden of malnutrition.